2007
DOI: 10.1203/01.pdr.0000290803.86985.61
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone (GH) Receptor C.1319 G>T Polymorphism, But Not Exon 3 Retention or Deletion Is Associated With Better First-Year Growth Response to GH Therapy in Patients With GH Deficiency

Abstract: ABSTRACT:We investigated possible influences of single nucleotide polymorphisms (SNPs) on first-year growth velocity in response to growth hormone (GH) therapy in GH-deficient (GHD) children. We recruited a total of 154 GHD prepubertal children who had undergone GH therapy for 1 y. To exclude the possibility that the genotype/allele variants influenced the height of GHD patients, we studied the same gene polymorphisms in 208 familial short stature (FSS) patients and 100 normal control individuals. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In most previous studies on the effect of the GHR exon 3 polymorphism on growth response in GHD patients, no association was reported, which is in agreement with our results [17,18,33,34,35]. However in a number of studies, including the study by Dos Santos et al [9], response to GH therapy was found to be more marked in patients carrying d3 homozygously or heterozygously.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In most previous studies on the effect of the GHR exon 3 polymorphism on growth response in GHD patients, no association was reported, which is in agreement with our results [17,18,33,34,35]. However in a number of studies, including the study by Dos Santos et al [9], response to GH therapy was found to be more marked in patients carrying d3 homozygously or heterozygously.…”
Section: Discussionsupporting
confidence: 92%
“…The distribution of GHR exon 3 isoforms in GHD in our study (28.4% fl/fl, 46.8% fl/d3 and 24.8% d3/d3) showed that the frequency of d3/d3 is higher and that of fl/fl is slightly lower than the distribution in most of the European studies which report a frequency of 43–55% in fl/fl, 36–47% in fl/d3 and 3–11% in d3/d3 [16,17,18,33,34,35,36]. …”
Section: Discussionmentioning
confidence: 94%
“…However, the c.1319 GOT polymorphism was found to be associated with therapeutic efficacy in GHD children (22). Additionally, other genes within the GH pathway may also be important, and this relative importance may differ between adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…Wan and coworkers examined the frequencies of 13 known SNPs of genes in this axis among 154 prepubertal children with GHD, 208 with familial short stature and 100 healthy children of normal stature [35]. SNPs of the following genes were evaluated: GHR, JAK2, STAT5a, STAT5b, IGF-I, IGFBP-3, ALS and SOCS-2.…”
Section: C1319 G>t Polymorphism In the Growth Hormone Receptormentioning
confidence: 99%